Video Promosi Ekowisata Kecamatan Kapur IX Kabupaten 50 Kota - Ozi Saputra; Jupriani Jupriani (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
promotional videos are used as a procces of forming a personal image or a place. The aim of this design is to produce a promotional media that is able to increase the number of tourists significantly, as well as provide information about various tourist attractions located in Kecamatan Kapur IX sub-district in the form of videos. The design method used is the 4-D method which has stages of definition, design, development, deployment. The data analis method uses SWOT to obtain the necessary data according to design needs. This promotional video for ecotourism in Kecamatan Kapur IX subdistrict goes through a creative program with pre-production, production and post-production stages. Results of designing a promotional videos as the main media for conveying information related to ecotourism in the Kecamatan Kapur IX sub-district so that is easy to understand and easy to access. Thispromotional videos also has other supporting media sucht as t-shirt, tote bags, stickers, posters, key chains and banner.